Sengketa Perebutan Divestasi Saham Newmont Nusa Tenggara: Analisis Ekonomi Politik (2008-2012) - Hafid Rahardjo (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
Competition to become the sole owner of Newmont Nusa Tenggara shares is very intense. Central government, local government, and house of representative are participating to obtain 31% shares of Newmont Nusa Tenggara, multinational corporation that operates in copper and gold mines. House of representatives is try to blocked the purchase of Newmont shares by government, with asking help from supreme audit agency (BPK) to support their claim. Specifically, based on this case, new tendency emerges in state capitalism in Indonesia, which is the emergence of capitalist and local government. This fierce competition between these actors proves that in Indonesia, the struggle to manage resource is not run by economic sense, but also political one.